Perencanaan Bisnis Pengembangan Klinik Fisioterapi Rumah Sakit Umum Prima Medika Denpasar Bali - Agung Manik Septiana Putra; Taufik Zulfikar; Rukhiyat Syahidin; Etty Sofia; Vip Paramarta (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to develop a business planning framework for the establishment of a Physiotherapy Clinic at Prima Medika General Hospital, Denpasar, Bali. The primary problem addressed is the growing demand for rehabilitation services that has not been optimally accommodated within the existing hospital structure. Using a qualitative descriptive evaluative approach, data were collected through in-depth interviews, field observations, and document analysis. The research focuses on market, human resources, and financial feasibility, alongside designing a business model through the Business Model Canvas (BMC) and analyzing competition using Porter’s Five Forces. Results indicate that the clinic development is feasible and holds strong potential when implemented in a phased manner. Key findings highlight a stable market demand from outpatients and institutional partners. Financially, the project is deemed viable with an Internal Rate of Return (IRR) of 18.19%. Integration with the hospital system provides a significant competitive advantage against industry rivals. This research offers practical insights for hospital management in strategic decision-making for new service development.